MAIN IDEA MEMORY STORAGE AS THE WAY TO TEACH READING COMPREHENSION FOR INDONESIAN EFL LEARNER - Doni Pesalozy (STKIP PGRI Lubuklinggau, 2019)
English is international language that used to communicate between people in the world with different language background. In Indonesia, English as foreign language that taught in the school, so all of Indonesian students learn English as the main subject lesson in the school. In learning process there are lot of difficulties that faced by students, one of them is reading, reading is process gaining the meaning in the text that conveyed by author, students must understand the meaning of the text both of lexical and phrase, so main idea memory storage as the best technique in teaching English h for the students